Palladium‐Catalyzed Three‐Component Tandem Reaction for One‐pot Highly Stereoselective Synthesis of (Z)‐α‐Hydroxymethyl Allylic Sulfones. Issue 4 (6th November 2017) - Hou, Yunlei; Shen, Qi; Li, Zefei; Chen, Shaowei; Zhao, Yanfang; Qin, Mingze; Gong, Ping
Abstract: A novel method is reported for the stereoselective synthesis of highly functionalized allyl aryl sulfones. This protocol is based on a Pd‐catalyzed three‐component tandem reaction of sulfonyl hydrazides and aryl iodides with allenes and exhibits high ( Z )‐selectivity, good yields, minimal waste, ample product scope, and operational simplicity. Abstract :